Penatalaksanaan Holistik dengan Pendekatan Dokter Keluarga pada Laki-laki Usia 50 Tahun dengan Hipertensi Primer - Efry Theresia Sianturi; Sahab H. SIbuea (CV. Jasa Sukses Abadi, 2021)
Hypertension is a global health problem resulting in an increase in morbidity and mortality and health costs, including in Indonesia, which can be handled by modifying lifestyle, including diet, exercise habits, stress, and smoking habits. Holistic and comprehensive family doctor approach in detecting internal and external risk factors, prioritizing patient-centered and family-approached is hoped to improve patient’s quality of life. This study is a case report. Primary data were obtained through history taking, physical examination and home visits. Secondary data were obtained from medical records of the patient at the health center. A 50-year-old man was diagnosed with primary hypertension since 5 years ago. Patient has taken anti-hypertension medicine but his lowest blood pressure is 140/80 mmHg. Internal risk factors, namely 50 years of age, male, overweight, curative medical seeking behavioral, inappropriate diet, does not know how to choose food based on nutrition fact labels, family history with hypertensive father and mother, and mother died of stroke. External risk factors, namely the lack of support from his brother regarding the patient's treatment and the length of his work for 10 hours a day. Non-medical and medical interventions were done on the patient and his family with education related to the patient's disease and the recommended dietary pattern in 3 home visits. The evaluation results obtained that complaints and worries of patients were reduced, the knowledge of patients and their families regarding hypertension increased and behavior related to hypertension improved.